2019
DOI: 10.1177/0013916518811418
|View full text |Cite
|
Sign up to set email alerts
|

Park and Neighborhood Attributes Associated With Park Use: An Observational Study Using Unmanned Aerial Vehicles

Abstract: As the world becomes more urbanized, neighborhood parks are becoming an increasingly important venue where people engage in physical and social activities. Using park-use data collected by unmanned aerial vehicles (UAVs), the aim of this study is to account for park use in light of park attributes and neighborhood conditions. The role of the built environment near a park receives particular attention as it is understudied in the literature. A regression model shows that neighborhood park utilization is positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…As this study associated the levels of use with the landscape features, the results are expected to be useful in design practice for promoting regular physical activity.Numerous studies have shown neighborhood parks provide ideal places for physical activity [19], emphasizing that the presence of or access to nearby nature can contribute to mental and physical health [20][21][22][23][24][25]. Compared with the large number of studies examining the influence of neighborhood-built environment on park usage [26,27], especially the proximity to a park and the surrounding communities [28][29][30], few studies have focused on the specific design features that may influence the park use and the occurrence of physical activity [31].Evidence shows that park attributes are related to park usage, that is, a large size, the quality of facilities, organized activities, and good maintenance can promote overall park use [31][32][33]. An observational study of plaza users in San Francisco found that the microclimate conditions, such as temperature, humidity, and sunshine, influenced the behaviors of visitors [34].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As this study associated the levels of use with the landscape features, the results are expected to be useful in design practice for promoting regular physical activity.Numerous studies have shown neighborhood parks provide ideal places for physical activity [19], emphasizing that the presence of or access to nearby nature can contribute to mental and physical health [20][21][22][23][24][25]. Compared with the large number of studies examining the influence of neighborhood-built environment on park usage [26,27], especially the proximity to a park and the surrounding communities [28][29][30], few studies have focused on the specific design features that may influence the park use and the occurrence of physical activity [31].Evidence shows that park attributes are related to park usage, that is, a large size, the quality of facilities, organized activities, and good maintenance can promote overall park use [31][32][33]. An observational study of plaza users in San Francisco found that the microclimate conditions, such as temperature, humidity, and sunshine, influenced the behaviors of visitors [34].…”
mentioning
confidence: 99%
“…Numerous studies have shown neighborhood parks provide ideal places for physical activity [19], emphasizing that the presence of or access to nearby nature can contribute to mental and physical health [20][21][22][23][24][25]. Compared with the large number of studies examining the influence of neighborhood-built environment on park usage [26,27], especially the proximity to a park and the surrounding communities [28][29][30], few studies have focused on the specific design features that may influence the park use and the occurrence of physical activity [31].…”
mentioning
confidence: 99%
“…However, this study attributed these features to park satisfaction, rather than park use. Furthermore, many more park features have been shown to be associated with park use that were not found in this study, such as playgrounds, table tennis tables, basketball courts, ponds and trees (Baran et al, 2014;Edwards et al, 2015;Park, 2019;Veitch et al, 2016). In this way, the evidence on park features, satisfaction and use remains rather mixed.…”
Section: Discussionmentioning
confidence: 57%
“…The use of public outdoor spaces increases with the land-use diversity factor; functional diversity and higher density development and a well-connected street network around the public space increase its use [42]. Work activities in public outdoor spaces, for instance, were facilitated by the provision of small tables and chairs with desk attachments, and business travelers surveyed in both outdoor and indoor areas at an airport stated that they needed at least comfortable seating and a place for their laptop in order to work properly [43].…”
Section: Discussionmentioning
confidence: 99%